2004
DOI: 10.1104/pp.103.032185
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Senescence and Response to Pathogens Is Altered in the Ascorbate-Deficient Arabidopsis Mutant vitamin c-1  

Abstract: The ozone-sensitive Arabidopsis mutant vitamin c-1 (vtc1) is deficient in l-ascorbic acid (AsA) due to a mutation in GDP-Man pyrophosphorylase (Conklin et al., 1999), an enzyme involved in the AsA biosynthetic pathway (Smirnoff et al., 2001). In this study, the physiology of this AsA deficiency was initially investigated in response to biotic (virulent pathogens) stress and subsequently with regards to the onset of senescence. Infection with either virulent Pseudomonas syringae or Peronospora parasitica result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(193 citation statements)
references
References 77 publications
8
181
0
4
Order By: Relevance
“…gmp1 silenced plants produced enhanced levels of ROS and reduced TMV accumulation. In agreement with this, previous reports had shown that reduced levels of GMP1 were associated with augmented basal defences mediated by SA and pathogenesis-related (PR) protein expression in A. thaliana (Barth et al, 2004;Pavet et al, 2005). Conti et al (2012) demonstrated that gmp1 silenced N. benthamiana plants also displayed an increased accumulation of PR proteins.…”
Section: Rna Interference-mediated Resistancesupporting
confidence: 76%
“…gmp1 silenced plants produced enhanced levels of ROS and reduced TMV accumulation. In agreement with this, previous reports had shown that reduced levels of GMP1 were associated with augmented basal defences mediated by SA and pathogenesis-related (PR) protein expression in A. thaliana (Barth et al, 2004;Pavet et al, 2005). Conti et al (2012) demonstrated that gmp1 silenced N. benthamiana plants also displayed an increased accumulation of PR proteins.…”
Section: Rna Interference-mediated Resistancesupporting
confidence: 76%
“…It has been reported that extreme levels of ROS can trigger the production of SA that in turn leads to more ROS via a self-amplifying loop, activating the oxidative cell death cycle (Overmyer et al, 2003;Kangasjärvi et al, 2005). Indeed, a previous study showed that the vtc1 mutant produces high levels of SA after inoculation with a pathogen (Barth et al, 2004). To assess whether a high level of SA was also present in the selenite-treated vtc1 mutant, we carried out semiquantitative RT-PCR to evaluate the expression of the PR1 gene, which encodes the SAresponsive PR1, which is frequently used as a marker for SA signaling (Cao et al, 1997).…”
Section: Optimal Levels Of Ros Are Necessary For Selenite Resistancementioning
confidence: 99%
“…cDNA from 0.3 mg of total RNA was used as template for each 100-mL PCR. Gene-specific primers used for PCR were 5#-ACCTTCTCCGCAACAAGTGG-3# and 5#-GAAGCTTGGTGGCTTGTAGG-3# for RBCS2B (Acevedo-Hernández et al, 2005), 5#-CAGCTTGCCCACCCATTGTTA-3# and 5#-GTCGTACGCA-CCGCTTCTTTCTTA-3# for SAG13 (Barth et al, 2004), and QuantumRNA 18S internal standards for 18S ribosomal RNA (Ambion). PCR was terminated after 12 cycles for RBCS2B, 18 cycles for 18S ribosomal RNA, and 26 cycles for SAG13.…”
Section: Semiquantitative Reverse Transcription-pcr Analysismentioning
confidence: 99%